Impact properties of kenaf fibre/X-ray films hybrid composites for structural applications - Rayney Azmi, Ahmad Mustafa; Hameed Sultan, Mohamed Thariq; Jawaid, Mohammad; Md Shah, Ain Umaira; Mohd Nor, Ariff Farhan; Abdul Majid, Mohd Shukry; Muhamad, Sallehuddin; Abu Talib, Abd. Rahim (Elsevier, 2019)
Most existing designs of high velocity impact resistant materials are either heavy or expen-sive, so in markets the demand for lighter and cheaper materials is always on the rise. Theaim of this work to investigates the effect of different projectile shape and impact veloc-ities on the energy absorption and compression after impact of kenaf/X-ray/epoxy hybridcomposites. Kenaf fibre treated with NaOH solution and perforated X-ray films were chosenas a reinforcement in the epoxy matrix to fabricate hybrid composites. The hybrid com-posites were fabricated using conventional hand lay-up method followed by compressionmoulding and were subjected to high velocity impact tests using a single stage gas gun.The pressure settings of the gas gun were varied as follows: 20 bar, 30 bar, 40 bar and 50 bar,while the projectiles used were of three types: blunt, hemispherical and conical ones. Afterthe high velocity impact tests, the composites underwent dye penetration inspection andwere subjected to compression after impact tests. The obtained results revealed that thehybrid composites subjected to high velocity impact with hemispherical projectile exhib-ited the highest energy absorption, compared to the conical and blunt geometry. On theother hand, the hybrid composites subjected to hemispherical projectile impact possessthe lowest residual strength compared to conical and blunt geometry. The dye penetrationtest as well as the visual inspection also revealed that the hemispherical projectile pro-duces the biggest damage compared to the other two projectile types. We concluded thatdeveloped kenaf/X-ray/epoxy hybrid composites suitable for ballistic applications.